Improved control of Rhizopus stolonifer - induced storage rot of peach with hot water and antagonistic yeast, Debaryomyces hansenii - GOUTAM MANDAL, DINESH SINGH* and (Indian Phytopathology, 2006)
Pesticide residue is a great concern in peach fruit, hence an alternative approach to control post harvest diseases of peach was studied. Fruits treated with hot water dip at 50Â°C for 3 min + bioagent Debaryomyces hansenii resulted in minimum incidence (55.2%) and infected area (3.36 cm2 ) of Rhizopus stolonifer. Spoilage of the fruit was reduced by 9 percent over control in hot water dip + D. hansenii after 30 days of storage under cool chamber while in ambient condition, minimum spoilage was found in D. hansenii (8.0%) treated fruit. Firmness of the fruit was slightly reduced after hot water treatment but it did not significantly influence the occurrence of mycoflora. Quality of the fruit like TSS, acidity was not affected by the hot dip treatment and D. hansenii either alone or in combination.